Handbook of Consult and Inpatient Gynecology - Brady, Paula C. (Springer International Publishing : Imprint: Springer, 2016)
This handbook is a high-yield guide to diagnosis and management of common gynecologic problems for clinicians, residents, and medical students. It is a concise guide to gynecologic practice in emergency and inpatient settings, designed to optimize patient safety and outcomes. Common gynecologic problems are presented, including acute pelvic pain, vaginal bleeding, ectopic pregnancy, adnexal masses and torsion, spontaneous abortion, and sexual assault. This book also surveys inpatient and post-operative care of gynecologic patients, and addresses complications and considerations specific to gynecologic oncology, urogynecology, and assisted reproduction. Each chapter offers definitions of core concepts, differential diagnoses, actions to take upon receiving the consult and assessing the patient, and key points for the history, physical, diagnostic work-up, and management. .